Performance of Modified Pediatric Early Warning Score in General Medical Conditions and Disease Subgroups - Chutima Phuaksaman MD; Paphawadee Sukboonthong MD (SAGE Publishing, 2022)
Numerous existing Pediatric Early Warning Scores (PEWs) have varying degrees of reliability and validity, which are used in variety diseases of patients. This study is a prospective diagnosis study which involved the pediatric nurse evaluation of patient status using modified Pediatric Early Warning Score (NU-PEWS) until the patient was discharged or transferred to PICU. A total of 824 pediatric patients were admitted, 407 participants were enrolled in this study. The NU-PEWS demonstrated the most accurate cut-off point at greater than 3, with 90.5% sensitivity and 89.1% specificity. The receiver operating characteristic (ROC) indicated positive results in the general medical condition (ROC 0.958), gastrointestinal, respiratory, and hematologic diseases (ROC 0.94-0.97) whereas lowest in neurological disease (ROC 0.843). This study validated that NU-PEWS has good performance in detecting deteriorating patients, and that prediction utilizations are good in almost every subgroup of disease, with the exception of neurological disease.